2009
DOI: 10.1515/cclm.2009.260
|View full text |Cite
|
Sign up to set email alerts
|

Serum free light chains: diagnostic and prognostic value in multiple myeloma

Abstract: Background: Measurement of serum free light chains (FLCs) has recently become available for the diagnosis and monitoring of patients with plasma cell dyscrasias. The aim of this study was to investigate the performance of the serum FLC assay as a tumour marker by comparing FLC concentrations with serum protein electrophoresis (PE) results in the diagnosis of multiple myeloma (MM). In addition, we also evaluated the prognostic value of the baseline serum FLC ratio in patients with MM. Methods: We measured FLC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
3
4
0
2
Order By: Relevance
“…The association with these parameters support the prognostic value of sFLC because they are indicative of higher tumour burden, deterioration of renal function and a more aggressive disease. Similar findings have been found previously [12,13]. Furthermore, a positive correlation was confirmed between sFLCR, free kappa and free lambda with plasma cell infiltration in bone marrow, creatinine and B2M (Table 2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The association with these parameters support the prognostic value of sFLC because they are indicative of higher tumour burden, deterioration of renal function and a more aggressive disease. Similar findings have been found previously [12,13]. Furthermore, a positive correlation was confirmed between sFLCR, free kappa and free lambda with plasma cell infiltration in bone marrow, creatinine and B2M (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…The results from this study confirmed the prognostic value of sFLCR in a cohort of patients in the southern area of Spain for the first time, with a cut-off sFLCR≥47 predicting a worse outcome. The sFLCR cut-off obtained in this study is higher than reported by Snozek et al (sFLC ratio <0.03 or >32) [11] and by Xu et al (sFLC ratio <0.04 or >25) [14], but it is close to that obtained by Sthaneshwar et al with median sFLC ratios of >57.5 and 0.04 for kappa and lambda secretors MM [13]. …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Схожие результаты были получены ранее в исследованиях F. van Rhee и соавт., P. Sthaneshwar и соавт. [20,21].…”
Section: случаи смерти / Deathunclassified
“…Основные исследования по изучению прогнос тической роли СЛЦ при ММ выполнены в Европе и США [15,16,[18][19][20][21][22]. В России прогностическая значимость СЛЦ у пациентов с ММ недостаточно из учена [13,[23][24][25] ввиду малой доступности определе ния данных показателей пациентам с ММ, что явилось основанием для проведения настоящего исследования.…”
Section: Introductionunclassified